The mechanosensitive protein ANTXR1 is involved in maintaining cartilage homeostasis in post-traumatic osteoarthritis - Miao, Zhuangzhuang; Liu, Junjie; Cheng, Pengfei; Shen, Yinghao; Tang, Jiahang; Zhu, Jiajie; Liu, Weiwei; Zhou, Xuchang; Jing, Hongying (Frontiers in Cell and Developmental Biology, 2025)
Post-traumatic osteoarthritis (PTOA) is a degenerative joint disease secondary to joint trauma, such as anterior cruciate ligament (ACL) injury. Our previous study found that the mechanosensitive protein ANTXR1 is involved in the regulation of bone homeostasis, however, whether ANTXR1 is involved in the regulation of cartilage homeostasis in PTOA is unclear. In this study, we focused on the expression of the mechanosensitive protein ANTXR1 in cartilage homeostasis and explored its role in the initiation and progression of PTOA. To investigate the effects of treadmill exercise on bone-cartilage homeostasis, we established models using different exercise intensities (20%, 40%, 60%, 80% of maximal oxygen uptake, VO2max). Histological staining (Hematoxylin and Eosin, HE) and micro-computed tomography (micro-CT) revealed that moderate-intensity exercise (40%–60% VO2max) effectively promoted bone-cartilage health compared to controls. Conversely, prolonged high-intensity exercise (8 weeks, 80% VO2max) demonstrated potentially deleterious effects on cartilage homeostasis. Immunofluorescence staining indicated that, compared to the sedentary group, both ANTXR1 protein expression in the knee cartilage was reduced across intervention groups, with expression levels progressively declining as exercise intensity increased. Notably, ANTXR1 and exhibited significantly higher expression in bone tissue compared to cartilage tissue. Bioinformatic analysis identified LRP6 as a potential target protein of ANTXR1. Furthermore, utilizing a post-traumatic osteoarthritis (PTOA) animal model, we explored the potential role of ANTXR1 in cartilage homeostasis and revealed that both ANTXR1 and LRP6 protein expression were significantly upregulated in the degenerating cartilage of PTOA rats. This study is the first to elucidate the dual roles of ANTXR1 in mechano-signaling and cartilage metabolic homeostasis, providing a molecular basis for developing ANTXR1-targeting inhibitors for PTOA treatment.